2012
DOI: 10.1007/s13277-012-0426-z
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin as an independent mortality predictor in patients with pancreas cancer. Results of a pilot study

Abstract: Prognosis of patients with pancreas cancer is very poor. The aim of the study was to test the significance of laboratory parameters in the prognosis of patients with pancreas cancer. The studied group included 57 patients (31 men, 26 women, mean age 65 ± 9 years). Blood was collected at the time of diagnosis of pancreas cancer and basic laboratory parameters, including nutritional and inflammatory markers and tumour markers were measured. Patients were followed up until death (median survival 147 days). Ferrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 16 publications
3
37
0
1
Order By: Relevance
“…Several forms of cancer including lung [17,18], pancreatic [19] colon [20][21][22][23], and breast cancer [20,[24][25][26][27] have been reported to exhibit significant levels of iron overload. Breast cancer cells have been shown to exhibit increased levels of hepcidin, ferritin, and labile iron along with decreased FPN expression [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several forms of cancer including lung [17,18], pancreatic [19] colon [20][21][22][23], and breast cancer [20,[24][25][26][27] have been reported to exhibit significant levels of iron overload. Breast cancer cells have been shown to exhibit increased levels of hepcidin, ferritin, and labile iron along with decreased FPN expression [24].…”
Section: Introductionmentioning
confidence: 99%
“…The standard serum marker in routine use for the management of PC is carbohydrate antigen 19-9 (CA 19-9). However, its inadequate sensitivity and specificity limit its use for the early diagnosis of PC [3]. The European Group on Tumor Markers (EGTM) reported that CA 19-9 could not be recommended for screening purposes, but only for monitoring response to therapy in patients who have elevated levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its well-recognized relationship with inflammation and malnutrition, recent reports have shown serum ferritin to be closely connected with the presence and prognosis of malignancies such as renal cell carcinoma, neuroblastoma, pancreatic cancer, and hematologic malignancies [7,[25][26][27] . Moreover, oxidative tissue damage was found to increase tissue ferritin synthesis as well as its secretion [28] .…”
Section: Discussionmentioning
confidence: 99%